Multiplex Fluorescent RT-PCR to Quantify Leukemic Fusion Transcripts - M. Dupont; A. Goldsborough; T. Levayer; J. Savare; J.M. Rey; J.F. Rossi; J. Demaille; T. Lavabre-Bertrand (BioTechniques)
The detection of chimeric transcripts derived from aberrant chromosomal fusion events provides an exceptionally valuable tool for the diagnosis of leukemia. We have developed a simple, inexpensive, reproducible, and automated method to quantify RT-PCR products. Our approach utilizes fluorescent PCR for the co-amplification of the specific fusion transcript with an internal control (HPRT). We have also combined the advantages of real-time quantitative PCR, namely continuous fluorescent detection of PCR products with the low cost of an endpoint assay by examining in a novel manner the amount of fluorescent PCR product generated during the exponential phase of amplification. This has been achieved by using the automated loading and quantification capacity of a laser-induced fluorescence capillary electrophoresis system, the ABI Prism® 310A, so that we can effectively monitor amplification during the exponential phase cheaply, reproducibly, and in a sensitive manner. We have carefully verified our new technique using five leukemia cell lines, each expressing a different fusion transcript. Specificity and reproducibility (CV within 10%) have been examined and demonstrate the excellent precision of our technology. The high sensitivity levels of at least 10-4 to 10-60 btained for the serial dilutions of the five cell lines validate the choice of our fluorescent PCR as a comparable method to other more complicated and expensive methods. Our results have allowed us to quantify PCR products and the amount of chimeric mRNA originating from the translocation breakpoint. We demonstrate that our novel fluorescent method is useful to detect and quantify residual leukemic cells in patients undergoing therapy.